ARE THERE BENEFITS IN PERFORMING GASTRO-OMENTOPEXY IN LAPAROSCOPIC VERTICAL GASTRECTOMY? - SOUZA,Maíra Danielle Gomes de (2021)
ABSTRACT Background: Gastro-omentopexy promotes the reconnection of the stomach to the gastroesplenic and gastrocolic ligaments and constitutes an alternative for the prevention of complications in laparoscopic vertical gastrectomy. Aim: To demonstrate the benefits of the gastro-omentopexy technique in patients undergoing sleeve gastrectomy, with possible reduction in postoperative complications. Methods: Prospective, non-randomized, case series type study, consisting of a clinical population of 179 patients who underwent the technique in 2018, with follow-up between 6-12 months in the postoperative period. Results: From the participants 71.5% were women, aged between 30-40 years (36.3%). As for the prevalence of complications in the postoperative period, the low prevalence was evident, with emphasis on readmission (1.1%); reoperation (1.1%); wound infection (1.1%); bleeding hemorrhage (0.5%); and stricture (1.1%). However, temporary symptoms were present such as nausea/vomiting, food intolerance, epigastric pain and feeling of fullness, right after surgery. Conclusion: The technique promoted a significant improvement in quality of life and control of comorbidities. In addition, it was associated with a low prevalence of stenosis, and with no fistula, making the method safer.